miRNA-451 inhibits proliferation and motility of the gastric cancer SGC-7901 cell line via targeting AKT-mediated signal pathway - Chen, Biao; Deng, Jun-Jian; Ge, Wei; Zheng, Yong-Fa; Cao, De-Dong; Xu, Ximing (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: miRNAs are a group of non-coding RNAs that play an important role in in regulating tumour development and progression. Recently, increased evidences have reported that altered miRNA-451 is implicated in carcinogenesis of various types of human cancer. However, the expression and roles of miRNA-451 in gastric cancer (GC) remain to be established. Methods: Quantitative reverse transcription polymerase chain reaction (qRT-PCR) assay was performed to measure the expression of miRNA-451 in GC tissue samples and cell lines. Then, the effects of miRNA-451 on growth, colony formation, apoptosis, migration and invasion of SGC-7901 cells were focused upon after transient transinfection of miRNA-451 mimics. Finally, the effects of miRNA-451 upregulation on AKTmediated signal pathway were also determined. Results: miRNA-451 was found to be significantly down-regulated in gastric cancer tissues and cell lines. In addition, Functional studies indicated that the forced expression of miRNA-451 could suppress cell proliferation, colony formation, cellular migration and invasion of SGC-7901 cells. Moreover, we uncovered that AKT-mediated signal pathway has been partially inactivated at post-transcriptional levels with upregulation of miRNA-451. Conclusions: These findings support the role of miRNA-451 as a regulator of GC progression partially via attenuating AKT-mediated signal pathway. Thus, miRNA-451 may become novel promising potential therapeutic targets for gastric cancer.